2020
DOI: 10.1016/j.celrep.2020.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Cdk4 and Cdk6 Couple the Cell-Cycle Machinery to Cell Growth via mTORC1

Abstract: Highlights d Cdk4/6 regulates mTORC1 activity via TSC2 d Cdk4/6 binds TSC2 and phosphorylates it on Ser1452 and Ser1217 d Cdk4/6 inhibitors also inhibit mTORC1 d Cdk4/6 couples cell-cycle progression via RB to cell growth via mTORC1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 49 publications
6
82
1
Order By: Relevance
“…Despite the direct interaction between cyclin D1 and TSC2 [55], the first to show a direct phosphorylation of TSC2 by CDK4 or CDK6 were Romero-Pozuelo et al in Drosophila [56]. Recently, they also found that cyclin D-CDK4/6 activates mTORC1 by binding and phosphorylation of TSC2 in multiple human and mouse cell lines and pharmacological inhibition of CDK4/6 leads to a rapid, TSC2-dependent reduction of mTORC1 activity [57]. In addition to these findings, another connection between CDK4 and mTORC1 activation was revealed.…”
Section: Amino Acids and Nucleotide Metabolismmentioning
confidence: 99%
“…Despite the direct interaction between cyclin D1 and TSC2 [55], the first to show a direct phosphorylation of TSC2 by CDK4 or CDK6 were Romero-Pozuelo et al in Drosophila [56]. Recently, they also found that cyclin D-CDK4/6 activates mTORC1 by binding and phosphorylation of TSC2 in multiple human and mouse cell lines and pharmacological inhibition of CDK4/6 leads to a rapid, TSC2-dependent reduction of mTORC1 activity [57]. In addition to these findings, another connection between CDK4 and mTORC1 activation was revealed.…”
Section: Amino Acids and Nucleotide Metabolismmentioning
confidence: 99%
“…The role of the CDK4/cyclin D-Rb axis on cell size regulation has been purported by studies from our lab and others (Ginzberg et al, 2018;Schmoller et al, 2015;. While the mechanisms by which CDK4 activity sets target size remains to be investigated, there is increasing evidence that inhibition of CDK4 activity results in increased biosynthetic capacity, such as mitochondrial size and activity, presumably through its feedback on mTORC1 signaling (Cretella et al, 2018;Franco et al, 2016;Haines et al, 2018;Jansen et al, 2017;Romero-Pozuelo et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…There is evidence that growth information can be integrated by Rb phosphorylation, as Rb inhibition has been shown to result in smaller cell size [138][139][140] and its overexpression, a larger cell size [141]. Recent work has proposed a link between CDK4/6 activity and mammalian target of rapamycin complex 1 (mTORC1), a key regulator of cell growth [142]. The mTOR protein kinase is a key part of a signalling network integrating environmental inputs such as amino acid and oxygen levels, with mTOR activity promoting protein, lipid and nucleotide synthesis and inhibiting autophagy [143].…”
Section: Cell Growth/sizementioning
confidence: 99%
“…The mTOR protein kinase is a key part of a signalling network integrating environmental inputs such as amino acid and oxygen levels, with mTOR activity promoting protein, lipid and nucleotide synthesis and inhibiting autophagy [143]. In addition to Rb phosphorylation, CDK4/6 may also promote mTor activity [142]. In this way, CDK4/6 could couple the cell cycle machinery and cell growth.…”
Section: Cell Growth/sizementioning
confidence: 99%